PEMBERIAN ASI EKSKLUSIF DENGAN PERTUMBUHAN BAYI USIA 0-6 BULAN - rukanah rukanah (Akademi Kebidanan Griya Husada Surabaya, 2019)
Introduction: Exclusive breastfeeding is a baby that is only given breast milk for 6 months without the addition of other liquids, such as formula milk, oranges, honey, tea water, and water and without adding food to, such as bananas, milk porridge, biscuits, rice porridge and rice team, except vitamins and minerals and drugs (Prasetyono, 2012). Method: The purpose of this study was to determine the relationship of exclusive breastfeeding with the growth of infants aged 0-6 months in Gempolpading Village, Pucuk District, Lamongan Regency. This study uses an observational analytic research design, with a cross sectional approach using primary data. The population of this study was all infants aged 0-6 months who were given exclusive breastfeeding in Gempolpading Village, Pucuk Subdistrict, Lamongan Regency with a total population of 20 infants and a sample of 20 infants. How to take samples using Nonprobability sampling with Total Sampling techniques. Then the data collected is processed using the Spearman Rank test. Results: From the Spearman Rank test results obtained p value (0,000) <? (0.05), then H1 was accepted meaning that there was a relationship between exclusive breastfeeding and the growth of infants aged 0-6 months in Gempolpading Village, Pucuk District, Lamongan Regency. Discussion: The conclusion of this study is that there is a relationship between exclusive breastfeeding and the growth of infants aged 0-6 months in Desa Gempolpading, Pucuk Subdistrict, Lamongan Regency. For this reason, it is expected that health workers will further increase their exclusive breastfeeding by providing counseling and understanding to mothers